Advanced Customer Return Process using SAP EWM-SD Integration - Venkateswara Rao Mekanaboina (International Journal of Computational and Experimental Science and Engineering, 2026)
The integration of SAP Extended Warehouse Management with SAP Sales and Distribution systems is a crucial feature of modern logistics companies. Constant technical connectivity eliminates manual data transfers, reducing errors and accelerating disposition decisions. The framework provides real-time visibility of the return operations, including the creation of return orders and the ultimate disposition of inventory, which fosters a feeling of transparency that improves operational efficiency and customer experiences. Standardized processes guarantee uniformity in the networks of facilities, and mobile technologies provide data capture and validation. The data of returns are transformed into predictive intelligence through advanced analytics to support proactive resource planning and strategic supply chain decisions. The incorporation of quality inspection improves the disposition determination by ensuring that goods are transported effectively to the appropriate places, such as restocking, refurbishing, or recycling. Automation of financial reconciliation ensures the consistency of the master data between physical inventory records and accounting systems to facilitate proper reporting and compliance. Sustainability-oriented models incorporate environmental aspects into the process of returns, which contributes to the initiatives of the circular economy. Continuous improvement methods allow incremental efficiency improvements to compound over time, creating competitive advantages. Fraud detection secures company assets and preserves the integrity of a return program. Companies that invest in a comprehensive SAP EWM-SD integration have quantifiable gains in terms of operational efficiency, financial performance, customer satisfaction, and environmental responsibility.